Manipulation of subcortical and deep cortical activity in the primate brain using transcranial focused ultrasound stimulation - Folloni, D; Verhagen, L; Mars, R; Fouragnan, E; Constans, C; Aubry, J; Rushworth, M; Sallet, J (Elsevier, 2019)
The causal role of an area within a neural network can be determined by interfering with its activity and measuring the impact. Many current reversible manipulation techniques have limitations preventing their application particularly in deep areas of the primate brain. Here we demonstrate focused transcranial ultrasound stimulation (TUS) protocol impacts activity even in deep brain areas: a subcortical brain structure, the amygdala (experiment 1), and a deep cortical region, anterior cingulate cortex (ACC, experiment 2), in macaques. TUS neuromodulatory effects were measured by examining relationships between activity in each area and the rest of the brain using functional magnetic resonance imaging (fMRI). In control conditions without sonication, activity in a given area is related to activity in interconnected regions but such relationships are reduced after sonication, specifically for the targeted areas. Dissociable and focal effects on neural activity could not be explained by auditory confounds.